Experimental Analysis of Reverse Micro-EDM for Machining Microtool. Issue 4 (11th March 2016) - Singh, Amit Kumar; Patowari, Promod Kumar; Deshpande, Nishikant V.
Abstract : High aspect ratio microtools find numerous applications in the production of miniaturized components and structures, e.g., drilling of microholes in ink jet nozzles, air bearings, and biomedical devices. The present study aims to machine microrods using reverse microelectrical discharge machining (R-μEDM) process. These microrods can be used as microtools for drilling microholes. A detailed experimental investigation has been carried out with the help of Taguchi's orthogonal array for understanding the mechanism of the process. The process parameters such as voltage, feed rate, and capacitance are considered to perceive their effect on response measures such as machining time, deviation in length, deviation in average diameter, standard deviation (SD) in diameter, and surface roughness. The optimal process parametric condition of R-μEDM has been determined for desired performance, i.e., obtaining the target length and average diameter of the microrod and ensuring its straightness with minimum time duration. Confirmation experiment has been carried out at the optimum condition and accordingly the results have been presented. Surface morphology of the machined microrod at the optimum condition has also been investigated. Microrod of diameter 170 µm with a high aspect ratio of 18 has been successfully machined using this process.